The Frequency but not the Phenotype of Circulating Peripheral T Helper Cells is Increased at Later Stages of Progression to Type 1 Diabetes - Schroderus, Anna-Mari; Hanel, Andrea; Vandamme, Celine; Pitkänen, Viola; Rytkönen-Nissinen, Marja; Heinäniemi, Merja; Knip, Mikael; Veijola, Riitta; Toppari, Jorma; Ilonen, Jorma; Lempainen, Johanna; Kinnunen, Tuure (WILEY, 2026)
Circulating follicular (cTfh) and peripheral (cTph) T helper cells have been demonstrated to be expanded in several autoimmune diseases, including type 1 diabetes (T1D). Here, we examined the frequencies and phenotypes of these cells at different stages of T1D development and addressed their phenotypic and clonal relationships by analyzing samples from 27 children with newly diagnosed T1D, 29 autoantibody-positive (AAb+) children who later progressed to T1D and 57 healthy, age-matched controls. Higher frequencies of cTph cells were detected in children with T1D and AAb+ children by flow cytometry, but no phenotypic alterations compared with cTph cells from healthy children were observed. Through a single-cell multiomics approach, we demonstrate that cTph cells appear phenotypically more heterogeneous compared with cTfh cells and that they exhibit phenotypic and clonal sharing with both cTfh as well as CXCR5−PD-1lo memory T cells. Finally, the frequencies of cTph or cTfh cells did not differ in 17 children analyzed during seroconversion for T1D-associated autoantibodies, the earliest detectable time point for autoimmunity. Collectively, our data demonstrate that cTph cells are a highly heterogeneous population partially sharing features with cTfh cells and that their frequency but not phenotype is altered at later stages of progression to clinical T1D.